2011
DOI: 10.4103/1119-3077.79230
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose improved glycemic control and the 10-year coronary heart disease risk profile of female type 2 diabetes patients in Trinidad and Tobago

Abstract: Provision of facilities for self-monitoring of blood glucose in Afro-Caribbean women with type 2 diabetes improves both their glycemic control and CHD risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Studies and systematic reviews have found that the prevalence of HBsAg among pregnant women in a collection of African nations varies from 2.4–16% [ 11 ]. For example, a study conducted among Sudanese pregnant women found a prevalence of 5.6%; [ 12 ] similar studies estimated a prevalence of 8.2% in Nigeria [ 13 ], 6.3% in Tanzania [ 14 ], 8.0% in Mali [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies and systematic reviews have found that the prevalence of HBsAg among pregnant women in a collection of African nations varies from 2.4–16% [ 11 ]. For example, a study conducted among Sudanese pregnant women found a prevalence of 5.6%; [ 12 ] similar studies estimated a prevalence of 8.2% in Nigeria [ 13 ], 6.3% in Tanzania [ 14 ], 8.0% in Mali [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…50 The retrospective observational ROSSO study found that SMBG was associated with reduced incidence of micro-and macrovascular events and all-cause mortality, irrespective of insulin use. [51][52][53] On the other hand, longitudinal observational data from the Fremantle Diabetes Study found that SMBG was not independently associated with improved survival, and there were inconsistent findings relating to the association of SMBG with cardiac death and retinopathy.…”
mentioning
confidence: 99%
“…Barnett et al 37 and Polonsky et al 38 reported that the SMBG/education combination led to significantly greater reductions in A1C than education alone. Ezenwaka et al 35 reported that the combination led to significantly greater decreases in A1C than usual care. The results of Kleefstra et al 36 were less clear.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies did not examine moderators. 35,37,39,40,42,44 Farmer et al 46 and Polonsky et al 38 investigated medication as a possible moderator and found that it did not affect the relationship between SMBG and A1C, nor did BMI, 36 duration of diabetes, 36,46 health status, or complications. 46 Kleefstra et al 36 found adherence to self-management intervention procedures unrelated to outcomes, but 2 studies indicated treatment adherence as a potential moderator, 39,43 echoing Surgeon General Koop’s statement that “[treatments] don’t work in patients who don’t [use] them.” 47…”
Section: Resultsmentioning
confidence: 99%